Pro-Productivity Institutions: Learning from National Experience - Renda, Andrea (OECD Productivity Working Papers, 2017)
This paper analyses and compares ten institutions that have a mandate to promote productivity-enhancing reforms. The selected bodies include government advisory councils, standing inquiry bodies, and ad hoc, temporary task forces. We find that well-designed pro-productivity institutions can generally improve the quality of the policy process and political debate, and can make a significant contribution to evidence-based policymaking. Our findings also support the view that concentrating knowledge and research on productivity in one independent, highly skilled and reputed body can help create the momentum and the knowledge that are required to embrace the challenging task of promoting long-term productivity growth. We also find evidence that while institutions located outside government have more leeway in promoting reforms that challenge vested interests and produce results over a time span that goes beyond the electoral cycle, the existence of smart government bodies can allow experimental policymaking and a more adaptive, evidence-based policy process. We also find that it is of utmost importance to provide these bodies with sufficient resources, skills, transparency and procedural accountability to fulfil their tasks; a sufficiently broad mission, oriented towards long-term well-being and at both supply-side and demand-side considerations; policy evaluation functions; and the ability to reach out to the general public in a variety of ways, from consultation to advocacy, use of social media, and other forms of communication